Test ogólnej kontroli dla umiędzynarodowienia konfliktu zbrojnego oraz określenia statusu ofiar w orzecznictwie Międzynarodowego Trybunału Karnego ds. zbrodni w b. Jugosławii: [Overall control test to internationalize an armed conflict] (Studia Prawnicze / The Legal Studies, 2011)
Międzynarodowy Trybunał Karny ds. Zbrodni w b. Jugosławii (MTKJ) został powołany do życia rezolucją Rady Bezpieczeństwa nr 827 (1993). Odnośnie MTKJ zamiar powołania Trybunału został wyrażony już w rezolucji nr 808 (1993). MTKJ został powołany dla osiągnięcia bardzo ważnych prawnych i politycznych celów: ukarania sprawców poważnych naruszeń międzynarodowego prawa humanitarnego popełnionych w byłej Jugosławii od 1991 r.; zapobieżenia kolejnym zbrodniom; usprawnienia procesu osiągania pokoju oraz służenia jako test na potrzeby przyszłego, stałego międzynarodowego trybunału karnego.The article presents so called overall control test to internationalize an internal armed conflict adopted in the International Criminal Tribunals for the former Yugoslavia (ICTY) jurisprudence. This test is used in order to hold an individual responsible for grave breaches of the Geneva Conventions of 1949. The article begins with the creation and jurisdiction of the ICTY. The overall control test is presented by invoking and analyzing representative judgments of the ICTY such as the Tadić case (Trial Chamber 1997 and Appeals Chamber 1999), the Aleksovski case (Appeals Chamber 200), the Blaskić case (Trial Chamber 2000) as well as the Kordić and Cerkez case (Trial Chamber 2001 and Appeals Chamber 2004). The Tadić case is also compared to the International Court of Justice (ICJ) Nicaragua case of 1986 where the ICJ used effective control test. The ICTY conclusions have been strongly criticized among the representatives of Polish and world doctrine (inter alia by W. Czapliński, T. Meron, M.P. Scharf, M. Sassoli and L. Olsen). Their views are included. The final remarks pertain to the ICJ judgment in the Bosnia and Herzegovina v. Serbia and Montenegro case of 2007 where the ICJ in a way tried to reconcile two opposite legal views stating that the overall control test from the Tadić case was adopted to different purpose (namely to define the nature on an armed conflict and when found to be an international one to hold an individual responsible for grave breaches of the Geneva Conventions of 1949) whereas the effective control test was created in order to hold a State responsible. In this case the ICJ decided to use the effective control test.